Recurrent MALAT1-GLI1 Oncogenic Fusion and GLI1 Upregulation Define a Subset of Plexiform Fibromyxoma - Spans, Lien (J Pathol, 2016)
Plexiform fibromyxomas are rare neoplasms, being officially recognized as a distinct entity among benign mesenchymal gastric tumors in the 2010 WHO Classification of Tumors of the Digestive System. Characteristically, these tumors have a multinodular/plexiform growth pattern, and histologically contain variably cellular areas of bland myofibroblastic type spindle cells embedded in an abundant myxoid matrix, rich in capillary-type vessels. As of yet, the molecular and/or genetic features of these tumors are unknown. Here, we describe a recurrent translocation t(11;12)(q11;q13) involving the MALAT1 (metastasis associated lung adenocarcinoma transcript 1) long noncoding gene and the GLI1 (glioma-associated oncogene homologue 1) gene in a subgroup of these tumors. The presence of the fusion transcript in our index case was confirmed using polymerase chain reaction on genomic DNA followed by Sanger sequencing. We showed that the truncated GLI1 protein is overexpressed and retains its capacity to transcriptionally activate its target genes. A specific FISH assay was developed to detect the novel MALAT1-GLI1 translocation in formalin-fixed paraffin-embedded material. This resulted in the identification of two additional cases with this fusion, and two cases with polysomy of the GLI1 gene. Finally, immunohistochemistry revealed that the GLI1 protein is exclusively overexpressed in those cases that harbor GLI1/12q13 genomic alterations. In conclusion, overexpression of GLI1 through a recurrent MALAT1-GLI1 translocation or GLI1 upregulation delineates a pathogenically distinct subgroup of plexiform fibromyxomas with activated Sonic Hedgehog signaling pathway.